"A rich storehouse for research": the historical development of the Western Cape Archives and Records Service - Hendrich, Gustav (Faculty of Humanities, University of the Free State, 2017)
Without the existence of archival repositories, or institutions responsible for the safekeeping and preservation of records, there will be no fundamental source for studying the past. The primary role of archives the world over is to preserve historical sources of information for the benefit of future generations. For understanding the South African past, particularly from its early beginnings at the Cape, the Western Cape Archives and Records Service (WCARS) in Cape Town, plays an instrumental role in the proper recordkeeping of some of our country’s most valuable and irreplaceable records. Despite the centuries of possible hazardous influences such as water, damp and weather damage to the paper-based sources, the oldest records have largely remained intact. The aim of this article is to describe the efforts of archivists and record their pleas for more effective storage space/locations. It is also intended to shed light on the historical development of WCARS as a renowned research institution that today serves the interests of a wide spectrum of the public; most notably academics, historians, scholars and family researchers from not only the Western Cape region, but also from across South Africa and abroad.
Keywords: Western Cape Archives and Records Service (WCARS); Cape Archives Repository; Recordkeeping; GM Theal; HCV Leibbrandt; CG Botha; Archival holdings; Roeland Street Prison